Experimental investigation on multi-blended binder mortars incorporating alum sludge ash - Virdi, Mehak (My University, 2024)
This study aimed at investigating the effect of different industrial waste materials as partial replacement of cement on strength and durability properties of mortar mix. For economical and sustainability of natural resources, use of some industrial waste can demonstrate numerous benefits for the construction industry. Therefore, in this study quaternary blended binder mortars are prepared by incorporating alum sludge (AS), dolomite powder and ground granulated blast furnace slag (GGBS) as partial replacement of cement. Mortar mixes were prepared with a water/binder ratio and binder to fine aggregate ratio of 0.30 and 1:3, respectively. Control and other mortar mixes were prepared by replacing cement by AS (5%, 10%, 15%, 20%), dolomite (10%) and GGBS (35%, 30%, 25%., 20%). The evaluated strength and durability performances of quaternary blended mortars included compressive strength, flexural strength, water absorption, porosity, sorptivity, SEM and sulphate resistance (immersed in sodium sulphate) solutions and water for 28 and 56 days. The results of compressive strength and flexural strength of mix A5D10G35 were at par with control mix at the age of 28 days. Higher replacement of AS more than 5% did not improved the results. Thus, from the study in can be concluded that the mix containing A5D10G35 in blended mortars excels for various engineering properties at 28 and 56 days.
Keywords: alum; sludge; ash; mortars